Hubungan Obesitas dengan Komplikasi Maternal dan Luaran Perinatal: Association of Obesity with Maternal Complication and Perinatal Outcomes - Laily Mulyani; Novia Fransiska Ngo; Riries Choiru Pramulia Yudia (Jurnal Sains dan Kesehatan, 2021)
Obesity is a global health problem which numbers continue to increase from year to year. Obesity is a risk factor for maternal complications and adverse perinatal outcomes. This systematic review aims to evaluate the association of obesity with maternal complications and perinatal outcomes. This systematic review was conducted by searching for studies on databases such as Pubmed, Google Scholar, Science Direct or Clinical Key and the studies observed are studies published in 2016-2020 in Indonesian and English. The results of the study search were obtained as many as 74 studies and 31 studies that met the inclusion and exclusion criteria of the study. Of the 31 studies examined, there were 16 studies that analyzed the associtation between obesity and preeclampsia, 25 studies that analyzed the association between obesity and gestational diabetes, 16 studies that analyzed the association between obesity and preterm birth, 15 studies that analyzed the association between obesity and fetal death, and 19 studies that analyzed the association between obesity and macrosomia. Based on this systematic review it can be concluded that obesity was associated with the incidence of preeclampsia, gestational diabetes, preterm birth and macrosomia. But, obesity was not associated with perinatal mortality.